Review of solvents based on biomass for mitigation of wax paraffin in Indonesian oilfield - Afdhol, M.K. (2019)
This paper presents a review of the expectations and challenges of using biomass in the prevention and slowing of paraffin wax deposition that takes place during the crude oil production process.